PENINGKATAN KEMAMPUAN DIGITALISASI ARSIP BAGI GURU SMK MPLB di CIKARANG, BEKASI, JAWA BARAT - Karomah, Nurul Giswi; Ferdinansyah, M; Andriani, Tri; Badriyah, Badriyah; Makmuroh, Umi Hanik (POLITEKNIK LP3I JAKARTA, 2023)
Based on government data, one of the contributors to the unemployment rate is vocational school graduates due to a lack of mastery in several new technologies, especially the digitization of archives. So, through this community service program, the Jakarta LP3I Politkenik has increased the ability to digitize archives for vocational school teachers in Cikarang. for MGMP Vocational School Teachers Department of Business Services Management (MPLB) Cikarang. This training aims to improve additional soft skills and hard skills and develop teaching skills for teachers. In the digital era, correspondence is an inseparable part. The use of digital letters should be done to reduce paper use and speed up the process of letters reaching the recipient. This training aims to create digital letters, archive letters, and send letters in digital form. The training was attended by 105 Vocational School Teachers who are members of the Cikarang MGMP Department (MPLB). The methods used are planning, implementation and observation. Apart from that, the cooperative learning method is used which aims to make participants active. The training evaluation was very good training, in terms of material and speakers. For the next program, a team was created to assist Cikarang MGMP Vocational School Teachers Department of Business Services Management (MPLB) regarding creating digital letters. Correspondence is an inseparable part of the Village Apparatus. The use of digital mail should have been done to reduce paper use and speed up., Key words: Training, Digitalization Archives